Islamic Religious Education Teachers' Resolutions to the Challenges of Learning Islamic Religious Education in the Era of the Industrial Revolution 5.0 at SMA Negeri 2 Kilo - Firmansyah Firmansyah; Muhammad Amin (STKIP Taman Siswa Bima, 2025)
Teacher resolution is a plan or movement of change carried out by teachers in the learning process in the classroom so that learning can run well. This study aims to identify what problems are faced by Islamic religious education teachers in Islamic Education learning in the era of the 5.0 industrial revolution and what causes obstacles or challenges in Islamic Education learning in the era of the 5.0 revolution, this study also aims to find out how teachers' resolutions are in facing the challenges of Islamic Education learning in the era of the 5.0 industrial revolution. The type of research in writing this thesis uses field research or case studies using observation, interview, and documentation data processing techniques and processing. The results of this study indicate that changes in the era can have a significant impact on the world of education, one of which is Islamic religious education learning. So that teacher resolution is very much needed and plays a very important role in overcoming teacher problems in Islamic Education learning. Thus it can be concluded that the Islamic Education teacher's resolution to the challenges of Islamic religious education learning in the era of the 5.0 industrial revolution at SMA Negeri 2 Kilo, Dompu Regency has been running well and has been well received by students by giving a positive response.